The mass movement and public policy: discourses of participatory democracy in post-1994 South Africa*. Issue 1 (2nd February 2017) - Brooks, Heidi
ABSTRACT: Despite policy commitments and legislated mechanisms, the system of participatory democracy in post-1994 South Africa is largely considered to have failed. In order to understand how underlying ideas can help to explain weaknesses in practice, this article examines how participatory democracy is understood by the ruling African National Congress (ANC). It shows that the multiple intellectual traditions shaping the participatory model have led to a set of policy initiatives that are not without internal tension. In part, the technocratic creep associated with improving public sector performance has stymied participatory efforts by placing efficiency and delivery over democracy and empowerment. Alongside this, however, the ANC's own conception of 'democracy' remains interwoven with its mass movement history – linking the role of popular participation to the extension of its own hegemony. The intent of policy to deepen democracy through structures of participatory governance is thus undermined by a teleological framing of participation as an intra- movement activity.